Substitutions, rendements d’utilisation et évaluation de la consommation d’énergie - Girod, Jacques (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractUse efficiency of the various forms of energy are essential parameters in the determination of useful energy consumption. Some authors (Adams and Miovic) have attempted to determine these by using econometric models instead of direct, and essentially technical, measurement. The paper presents this last method and insists on the fact that a correct determination of use efficiency requires that we distinguish between fossil fuels and electricity. Some results concerning the rate of substitution between the different forms of energy are provided.